Is mimicry a diversification-driver in ants? Biogeography, ecology, ethology, genetics and morphology define a second West-Palaearctic Colobopsis species (Hymenoptera: Formicidae). Issue 4 (17th July 2021) - Schifani, Enrico; Giannetti, Daniele; Csősz, Sándor; Castellucci, Filippo; Luchetti, Andrea; Castracani, Cristina; Spotti, Fiorenza A; Mori, Alessandra; Grasso, Donato A
Abstract: The West-Palaearctic Colobopsis ant populations have long been considered a single species ( Colobopsis truncata ). We studied the diversity of this species by employing a multidisciplinary approach and combining data from our surveys, museum and private collections, and citizen science platforms. As a result, we have revealed the existence of a second species, which we describe as Colobopsis imitans sp. nov., distributed allopatrically from Co. truncata and living in the Maghreb, Sicily and southern Iberia. While the pigmentation of Co. truncata is reminiscent of Dolichoderus quadripunctatus, that of Co. imitans is similar to Crematogaster scutellaris, with which Co. imitans lives in close spatial association, and whose foraging trails it habitually follows, similar to Camponotus lateralis and other ant-mimicking ants. The isolation between Co. imitans and Co. truncata seems to have occurred relatively recently because of significant, yet not extreme, morphometric differentiation, and to mtDNA polyphyly. Both Co. imitans and Co. truncata appear to employ mimicry of an unpalatable or aggressive ant species as an important defensive strategy; this 'choice' of a different model species is motivated by biogeographic reasons and appears to act as a critical evolutionary driver of their diversification.